Interpreting water: the human right to water under the Namibian constitution - Ndeunyema, N (2019)
In this thesis, I argue that a court enforceable human right to water can be implied from the right to life in Article 6 of the Namibian Constitution. The thesis achieves this through an elaborate interpretative examination and comparative analysis, principally invoking the African value of ubuntu. Ubuntu—which is legally developed through its four key principles of community, interdependence, dignity and solidarity—is anchored in a novel approach to Namibian Constitutional interpretation that I coin and substantively conceptualise as ‘re-invigorative constitutionalism’. The thesis also advances the ‘AQuA’ (Adequacy—Quality—Accessibility) content of water and articulates the various correlative duties within the context of the respect—protect—fulfil trilogy, duties that are imposed upon the Namibian State as the primary duty bearer for the right to water. These duties include irreducible essential content duties that are argued to be immediate when compared to general obligations. Critical recourse is had to the international law interpretative resources of the CESCR’s General Comment No. 15 on the right to water, the African Commission’s Nairobi Principles and the WHO’s Drinking-water Quality Guidelines. Moreover, the thesis addresses the various justiciability concerns that may arise, arguing that Namibian courts are indeed institutionally competent and legitimate in enforcing right to water claims through the application of the bounded deliberation model. It also argues that because the Principles of State Policy in Article 95 are rendered court unenforceable by Article 101, it does not undermine the claim that the right to water, anchored in the right to life, can be enforced in the courts. This is in light of the Article 95(j) PSP for the State to raise and maintain an acceptable standard of living, which would include water as a socio-economic good. The thesis additionally demonstrates the normative merits in courts’ affirming water’s justiciability as a human right.